Recreation facilities monitoring system using Entity Relationship Diagram (ER Diagram) / Norsyazlin Mohd Rosli, Amelia Ahmad and Nur Shaffiqa Muhammad Soffian - Mohd Rosli, Norsyazlin; Ahmad, Amelia; Muhammad Soffian, Nur Shaffiqa (2021)
This paper emphasises on the process of database formation for recreational facility elements using the Entity Relationship Diagram (ER Diagram) method as related to the study area in Seri Iskandar. It is designed to assist the local authority, namely Majlis Daerah Perak Tengah, to collect and store the data of recreational facilities elements in order to facilitate local authority to update and monitor the elements of the area. The formation of the illustration of ER Diagrams in this study is using the concept introduced by Chen in 1976. It is an illustrative diagram that includes three main stages, namely identifying the type of data required, forming entities and attributes and identifying the relationship between the entities.